Performance of blockboard using particle composite bagasse waste as core layer materials - Indra, Mawardi; Nurdin, N.; Fakhriza, Fakhriza; Ali, Jannifar; Hanif, Razak; Putra Jaya, Ramadhansyah (SAGE Publications Ltd, 2024)
Using wood as the core blockboard material has affected forest exploration, which causes damage to the ecosystem and the environment. The availability of large amounts of bagasse and styrofoam waste has become a potential alternative to replace wood. This study evaluates the properties of blockboards made from a composite of bagasse waste particles as the core layer, combined with thin plywood as the face layers, and styrofoam waste as the matrix for the bagasse particle composites. The blockboards were prepared through cold compression, and the effects of particles size and the ratio of particles to styrofoam on physical and mechanical properties such as density, moisture content, water resistance, bending strength, internal bond, and screw withdrawal resistance were investigated. The results demonstrated a linear improvement in both physical and mechanical properties with an increase in styrofoam content and a decrease in the particle size of bagasse. The blockboard with fine particles and 70 wt % of styrofoam exhibited the highest density of 0.59 g/cm3, moisture content of 8.54%, water absorption resistance of 33.71%, bending strength of 11.88 MPa, internal bond of 0.64 MPa, and screw withdrawal of 823.36 N. An increase in the density of the core layer was found to enhance all physical and mechanical properties of the blockboard. Consequently, the blockboard produced exhibits the potential to serve as an alternative to traditional blockboards.